IMPROVING THE STUDENTS’ SPEAKING SKILL BY USING TASK- BASED APPROACH AT THE SECOND YEAR STUDENTS OF SMA NEGERI 2 SUNGGUMINASA KAB. GOWA - Latief, Hasnawati; Muhsin, Muh. Arief (Fakultas Keguruan dan Ilmu Pendidikan, 2015)
This research aimed to find the improvement of the students’ speaking Accuracy and Fluency by using Task-based Approach at SMA Negeri 2 Sungguminasa Kab. Gowa in the 2013/2014 Academic Year. Task-based Approach was used in a Classroom Action Research (CAR). The research had been conducted in two cycles, each cycle consists of four meetings. It employed speaking test as an instrument. A number of research subjects were 37 students in class XI. The instruments were speaking test and observation. The research findings showed that Task-based Approach could improve the students’ speaking skill from cycle I to cycle II. The students’ achievement from D-Test to cycle I was 12.50%, and after finishing cycle II the students’ achievement became 16.27%. Based on the research findings, the researcher concludes that Task-based Approach gave a significant contribution in the learning process of speaking accuracy and fluency.